UNIQUE ORE COMPLEXES IN THE NORTHWESTERN SECTOR OF THE PACIFIC ORE BELT - Volkov A.V.; Sidorov A.A.; Tomson I.N.; Savva N.E. (My University, 2004)
Using hierarchic ore-formation analysis methods it is shown that thin sulfidization zones in several regions represent the formations, whose composition most fully reflects mineralogical types of polychronous and monochronous ore-formation series (ore complexes). All members of the particular series possess certain indices of mutual mineralogical-geochemical relationship. It is shown that the large thin fluidization zones in terrestrial and volcanic-origin rock massifs have, apparently, different nature - from hydrothermal-sedimentary to epigenetic (plutonic-fluid). These, practically non-investigated zones, are the most important ore substance sources at porphyric and vein field formation. Together with many satellite deposits, including monochroous copper-, gold-, tin-porphyric series, they form unique ore complexes or polychronous ore-formation series.